1982
DOI: 10.1063/1.330928
|View full text |Cite
|
Sign up to set email alerts
|

Ion-implanted magnetostatic wave reflective array filters

Abstract: A simple method for the determination of doping type in nanomaterials based on electrical response to humidity Appl. Phys. Lett. 101, 142110 (2012) Tunable nonlinear optical absorption in semiconductor nanocrystals doped with transition metal ions J. Appl. Phys. 112, 074305 (2012) Determination of the effective distribution coefficient (K) for silicon impurities J. Renewable Sustainable Energy 4, 043118 (2012) Lattice mismatch and crystallographic tilt induced by high-dose ion-implantation into 4H-SiC J. Ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
2

Year Published

1984
1984
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 7 publications
0
9
0
2
Order By: Relevance
“…The concept of spin-wave guiding in in-plane magnetised films using magnetisation gradients can be extended to the nanoscale (using e.g. ionic implantation [37][38][39]) and is promising for the realisation of magnonic networks for novel computing concepts. Moreover, the proposed approach is applicable for the guiding of waves in strongly-anisotropic media independently on the nature of these waves.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of spin-wave guiding in in-plane magnetised films using magnetisation gradients can be extended to the nanoscale (using e.g. ionic implantation [37][38][39]) and is promising for the realisation of magnonic networks for novel computing concepts. Moreover, the proposed approach is applicable for the guiding of waves in strongly-anisotropic media independently on the nature of these waves.…”
Section: Discussionmentioning
confidence: 99%
“…. При изготовлении МК из пленок железо-иттриевого граната (ЖИГ) формирование периодической структуры может осуществляться за счет изменения геометрических параметров -толщины пленки [3,4] или ширины вырезанного из пленки волновода [5], магнитных параметров [6], помещения пленки в периодически изменяющееся магнитное поле [7] или размещения на поверхности пленки периодической решетки из металлических [8][9][10][11] или полупроводниковых [12] элементов.…”
Section: Introductionunclassified
“…Отметим, что в случае формирования на поверхности пленок ЖИГ решеток из проводящих элементов их влияние в зависимости от проводимости σ и толщины t проводника на распространение ПМСВ может проявляться либо за счет модуляции дисперсии волны под металлом [3][4][5][6][7][8][9][10], либо за счет модуляции коэффициента затухания ПМСВ [12]. Так, например, в случае периодической решетки из металлических полосок при их толщине t > l s , где l s -глубина скин-слоя, магнонный кристалл формируется за счет изменения скорости МСВ на " металлизированных" участках пленки.…”
Section: Introductionunclassified
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] It has been shown that a single scatterer, for instance, a thin wire sitting on top of a ferromagnetic film that carries a DC current, creates a strongly localized magnetic field from which an incident plane backward volume magnetostatic spin wave (BVMSW) can efficiently scatter. 12,13 Two regimes were identified in this case; one is tunneling, when the area of field nonuniformity acts as an energy barrier for spin waves (magnons), and the only way for a wave to cross the nonuniformity is by tunneling. 13 The energy barrier is formed because the spin wave spectrum in an in-plane magnetized ferromagnetic film is characterized by an energy gap due to Zeeman and shape anisotropy contributions to spin wave dispersion.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, there is no second boundary of the nonuniformity, contrary to the cases of localized inhomogeneities studied before. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18] This allows us to produce quasianalytical expressions for the transmission and reflection coefficients for the step. We utilize a similar integration technique found in prior work that involves a Green's function of spin wave excitation.…”
Section: Introductionmentioning
confidence: 99%